Protective and risk factors of social support for healthcare workers in high-pressure occupational settings - Gui, Jingtao; Liang, Kaiwen; Yang, Yahui; Du, Lian (Frontiers in Psychology, 2025)
BackgroundSocial support is a critical factor in maintaining the mental health of healthcare workers in high-pressure occupational settings. However, few studies have systematically explored the different types of social support and their influencing factors. This study aims to investigate the current status of social support for healthcare workers under high pressure, along with the related protective and risk factors.MethodsThis cross-sectional study collected data through an online questionnaire involving 625 doctors and nurses from the First Affiliated Hospital of Chongqing Medical University. The Social Support Rating Scale (SSRS) was used to assess levels of social support, including objective support, subjective support, and support utilization. Data analysis was conducted using SPSS 26.0, employing univariate and linear regression analyses to examine gender differences and the impact of various factors on social support.ResultsThe study found that the total social support score was increased by factors such as family cohesion, living with others, older age, and professional identity (with doctors achieving higher scores than nurses), while insecure attachment and being an only child reduced the total social support score.ConclusionThis study reveals the multidimensional impact of various factors on social support for healthcare workers in high-pressure occupational settings. These findings provide a basis for promoting individual mental health and also highlights the need to pay more attention to the mental health of those healthcare workers with poor interpersonal relationships, younger individuals, and nurses in high-pressure environments.